The impact of stable atmospheric boundary layers on wind-turbine wakes within offshore wind farms. Issue 144 (September 2015) - Dörenkämper, Martin; Witha, Björn; Steinfeld, Gerald; Heinemann, Detlev; Kühn, Martin
Abstract: In terms of predicting wind turbine wakes, the stably stratified atmospheric boundary layer (SABL) is taking an exceptional position as wake effects and thus loads on subsequent turbines are stronger. In this study we show the impact of the SABL on power production and wake effects (power deficits) in offshore wind farms by means of measurements as well as large-eddy simulations (LES). Measurements show enhanced wake effects in the SABL compared to the unstable situation. Another influence on the power generation of an offshore wind farm is the distance of the wind farm to the shore. This is accounted for in the LES by a modification of surface characteristics at the coastal discontinuity. In addition to the effect of the coast, the numerical case study also shows the existence of local jets between the turbines of the wind farm.